1993
DOI: 10.1161/01.atv.13.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment of growth hormone-deficient adults results in a marked increase in Lp(a) and HDL cholesterol concentrations.

Abstract: The effects of growth hormone treatment of adults with adult-onset pituitary insufficiency on lipoproteins and apolipoproteins were investigated. Nine patients, one women and eight men (age range, 34-58 years), who had been treated for pituitary tumors were studied. They had complete pituitary insufficiency with a duration of at least 1 year. All patients received replacement therapy with thyroid hormones, glucocorticoids, and gonadal steroids. The study had a double-blind, placebo-controlled, crossover design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
111
7
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(141 citation statements)
references
References 47 publications
20
111
7
3
Order By: Relevance
“…Increase of plasma triglycerides or VLDL-triglyceride concentration and lowering of plasma HDL-cholesterol concentration are commonly found in insulin-resistant individuals with obesity or type 2 diabetes (37). As observed in several studies, Lp(a) increased during GH substitution (38,39) but no difference between the GH-deficient group and the control group could be found at the end of the study, questioning the clinical importance.…”
Section: Discussionmentioning
confidence: 69%
“…Increase of plasma triglycerides or VLDL-triglyceride concentration and lowering of plasma HDL-cholesterol concentration are commonly found in insulin-resistant individuals with obesity or type 2 diabetes (37). As observed in several studies, Lp(a) increased during GH substitution (38,39) but no difference between the GH-deficient group and the control group could be found at the end of the study, questioning the clinical importance.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, increased total cholesterol, LDL-C, apo-B levels, triglycerides and lipoprotein(a) levels, and a normal or decreased HDL-C, were found in GH deficient patients. [61][62][63] Also, increased peripheral insulin resistance and impaired glucose tolerance were observed in these subjects. 64 Accordingly, GH deficiency might be involved in the development of the components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 85%
“…In a double-blind placebo-controlled study on 22 patients with hypopituitarism, Weaver et al (18) found no significant increase in Lp(a) after 6 months of GH treatment, but in a subgroup of eight patients who received GH for a total of 12 months a modest but significant rise in Lp(a) was observed. In a double-blind, cross-over study of GH treatment in GHD adults, Eden et al (19) reported a marked almost twofold increase in Lp(a) after only 6 weeks of treatment, which was sustained after 26 weeks. However, in a double-blind placebo-controlled trial on 18 patients with severe GHD no significant effect of GH replacement was observed after 2 months of treatment (20).…”
Section: Introductionmentioning
confidence: 99%